(3fhQ GdHUGFQ hGdEHUGQ aj ehdO GdfHi GdeNJGQs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfGQ GdhLhO HehdO GdfHi GdeSYhO CeG HYO gPG eNJUQ dWja ai HjGf eG jJYdb HGdeUWai Udi Gddg Ydjg hSde ef CMhGdg GdTQjaI hTeGFdg s
(3BNQgG (B:s
(3aCNP GdCfHjGA GdYgO hGdejKGb Ydi Ceege HPdc Cf XgQ eMeO Udi Gddg Ydjg hSde djheff Hg hdjfUQfg agh SjO GdeQSdjf hEeGe GdfHjjf Udi Gddg Ydjg hYdi Bdg hUMHg CLeYjf hgPG eG CQOJ PcQg ai gPg GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs